Providing Psychological Nursing Care at Mental Rehabilitation Clinic, Addressing Self-Concept Challenges: Low Self-Worth Alongside a Bipolar Diagnosis - Permana, Gin Gin Sugih (CV. Literasi Publikasi Indonesia, 2024)
It is acknowledged that mental health plays a significant role in overall health. A person who is mentally disturbed and unable to function normally is said to have a mental disorder. This case study aims to provide an overview of mental nursing care for clients with low self-esteem, including assessment, diagnosis, intervention, implementation, and evaluation. The study employs a descriptive method, utilizing case studies, data collection techniques, observation, interviews, and a literature review to examine nursing acts that empower clients to recognize and utilize their strengths. The goal is to promote collaboration among rehabilitation clinics, professional organizations, families, and healthcare workers to deliver effective nursing care for mental health conditions, ultimately enhancing the well-being of individuals with low self-esteem and bipolar disorder.